Polarization anisotropy in nanowires: Fundamental concepts and progress towards terahertz-band polarization devices. (August 2022) - Johnston, Michael B.; Joyce, Hannah J.
Abstract: Pronounced polarization anisotropy in semiconductor nanowires has been exploited to achieve polarization-sensitive devices operating across the electromagnetic spectrum, from the ultraviolet to the terahertz band. This contribution describes the physical origins of optical and electrical anisotropy in nanowires. Polarization anisotropy arising from dielectric contrast, and the behaviour of (nano)wire grid polarizers, are derived from first principles. This review discusses experimental observations of polarization-sensitive light–matter interactions in nanowires. It then describes how these phenomena are employed in devices that detect or modulate polarized terahertz radiation on ultrafast timescales. Such novel terahertz device concepts are expected to find use in a wide variety of applications including high-speed terahertz-band communications and molecular fingerprinting.